Terapi Aktivitas Kelompok Dengan Permainan Tebak Gambar Guna Asah Kognitif Pada Lansia Di Panti Werdha - Khoiriyyah; Rina Puspita Sari; Kurnia; Laeliyah Kodriatul Fadillah; Meilinda Anisa Dewi; Neneng Mariah; Nur Septia Dewi Saputri; Nur Tahtiyah; Pandu Putra Darmawan; Ismi Nur Faizah (Yayasan Inspirasi El Burhani, 2025)
Introduction: To overcome and slow down the decline in cognitive function, one of the approaches used is through cognitive stimulation activities that are fun and easy to follow, such as picture guessing exercises. Thus, guess the picture is one of the potential methods to hone the memory and concentration of the elderly in social institutions such as the Orphanage Kasih Ayah Bunda. Objective: The purpose of group activity therapy with picture guessing games is to improve memory and concentration training. Method: This group activity therapy is divided into 4 stages, namely, the preparation stage, the administration of group activity therapy (TAK), the implementation of TAK and final reporting. Result: participants in this activity totaled 11 people. In the initial assessment using the Short Portable Mental Questionnaire (SPMSQ), 11 elderly people were identified as having moderate intellectual damage, and after the intervention, 6 elderly showed improvement to mild intellectual damage. Meanwhile, based on the assessment using the Mini-Mental State Examination (MMSE), from 4 elderly people with severe cognitive impairment and 7 with moderate impairment before the intervention, to 9 elderly people with moderate impairment and only 2 with severe impairment after the intervention. Conclusion: The results of the study of the cognitive function of the elderly showed a significant improvement after the intervention. Based on measurements using SPMSQ and MMSE, most participants showed improvements in cognitive function, with a shift in the category of milder cognitive impairment.